Psychological Distress Among Women Healthcare Workers: A Health System's Experience Developing Emotional Support Services During the COVID-19 Pandemic - Jesse Sanford; Alpna Agrawal; Alpna Agrawal; Alpna Agrawal; Karen Miotto (Frontiers Media S.A., 2021)
Ensuring the mental health and well-being of the healthcare workforce globally, especially women healthcare workers (HCWs), is an ongoing challenge that has been accentuated by the novel coronavirus (COVID-19) pandemic. Already at high risk of experiencing symptoms of stress, burnout, and depression, women HCWs are now also facing the psychosocial impacts of the COVID-19 pandemic. Although different types of mental health interventions have been introduced to support HCW well-being, the current needs of women HCWs have not been emphasized and replicable processes for developing and implementing specific emotional support services for women HCWs have not yet been well-described in the literature. Therefore, in this perspective, we discuss the approach our institution (University of California, Los Angeles) took for developing emotional support services for women HCWs that incorporate aspects of disaster behavioral health models and address various barriers to support and treatment. In addition, we describe and illustrate the process that we utilized to develop individual-level and institutional-level emotional support services. Finally, based on our institution's experience, we share recommendations for developing emotional support services for women HCWs during the COVID-19 pandemic and other future crises.